(untitled) (Semiárida, 2025)
Chubut River crosses the same name province, from its mountain range to its mouth in the Atlantic Ocean. Along its course, it runs across unpopulated areas until it reaches Embalse Ameghino, where its flow gets regulated and from where the Lower Valley of the Chubut River (VIRCh) develops. In this region, the river is channeled to supply the irrigation system that operates from October to March and serves as the main source of drinking water. Productive activities such as livestock farming and agriculture take place along the riverbanks. Given the multiple uses and services this common good provides to communities and considering future projections of reduced flow due to climate change, this study aims to implement a monitoring program to control river water quality. The program involves systematic sampling and seasonal assessment of physical, chemical, and biological parameters over two years. Subsequently, temporal and spatial differences are to be assessed using non-parametric statistics, and data structure and potential groupings are to be explored and synthesized through multivariate analysis techniques (Principal Component Analysis followed by non-hierarchical cluster analysis). Preliminary results show temporal differences in most of the parameters measured, indicating an impact of the irrigation system on river water quality. Additionally, three groups are identified: one corresponding to winter and two to spring, associated with sites from two spatially separated sections linked to different riverbank activities. Present findings reflect the influence of the irrigation system on water quality and of productive and urban activities along the river margins.